Differential nitric oxide levels in the blood and skeletal muscle of Type 2 diabetic subjects may be consequence of adiposity: a preliminary study. - Krause, M.; Rodrigues-Krause, J.; O'Hagan, C.; De Vito, G.; Boreham, C.; Susta, D.; Newsholme, Philip; Murphy, C. (W.B. Saunders Co., 2012)
Background and Aims: Nitric oxide (NO) exerts key regulatory functions including vasodilation and glucose uptake. Thus reduced NO levels are associated with insulin resistance and hypertension. In this preliminary work we aimed to measure the levels of NO• metabolites in serum and skeletal muscle of obese and non-obese subjects, with or without type 2 diabetes mellitus (T2DM). Methods: Fifteen sedentary male participants [7 obese controls (C) vs 5 obese and 3 non-obese T2DM; age 54 ± 9 years] were selected according to their BMI (> 30 kg/m2 for obese and 23–27 kg/m2 for non-obese participants) and evaluated for fasted values of blood glucose, HbA1c, lipid profile, serum CRP (C-reactive protein), erythrocyte glutathione (GSH) metabolism, plasma adiponectin, leptin and cytokines (TNF-α and INFγ), serum and skeletal muscle nitric oxide metabolites (nitrite and nitrates; tNOx) and skeletal muscle nNOS and iNOS expression. Body composition was measured by whole body DEXA and muscle microbiopsy was performed in the vastus lateralis. Results: We found that serum tNOx (total nitrite/nitrate; μmol/L) was lower in obese T2DM group (12.7 ± 3.5) when compared with their controls (21.1 ± 2.4), although the non-obese group presented higher concentration of tNOx (33.8 ± 7.2). Skeletal muscle nNOS was higher in obese controls, lower in non-obese T2DM and undetected in obese T2DM. On the other hand, expression of iNOS had an inverse relationship with nNOS, showing higher expression in obese T2DM, decrease in non-obese T2DM and absence in obese control group. tNOx levels (μmol/mg protein) were decreased in the non-obese T2DM group (12.07 ± 0.59) when compared with the obese control (21.68 ± 6.2) and the obese T2DM group (26.3 ± 7.26).Conclusion: We conclude that the decreased serum NO production in obese T2DM patients seems to be associated with adipose mass as lower adiposity was associated with normal NO which was reduced in the skeletal muscle of the non-obese T2DM patients. We suggest that the lower adiposity (and higher adiponectin) in non-obese T2DM could be responsible for differential levels of NO production and insulin resistance.